2007
DOI: 10.1016/j.ypmed.2006.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Use of preventive care by the working poor in the United States

Abstract: Objective-Examine the association between poverty and preventive care use among older working adults.Method-Cross-sectional analysis of the pooled 1996, 1998 and 2000 waves of the Health and Retirement Study, a nationally representative sample of older community-dwelling adults, studying self-reported use of cervical, breast, and prostate cancer screening, as well as serum cholesterol screening and influenza vaccination. Adults with incomes within 200% of the federal poverty level were defined as poor.Results-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 29 publications
1
34
0
Order By: Relevance
“…Temporal patterns of PCa screening by SES in Switzerland have not been investigated, which is of particular interest given that the use of PCa screening has been shown to vary by SES in other developed countries (Carrasco-Garrido et al, 2014;Dimitrakaki et al, 2009;Ross et al, 2007;So et al, 2014;Tabuchi et al, 2015;Weber et al, 2013). In general cancer screening is most frequent among individuals belonging to high SES because of better knowledge and higher access to medical care.…”
Section: Introductionmentioning
confidence: 99%
“…Temporal patterns of PCa screening by SES in Switzerland have not been investigated, which is of particular interest given that the use of PCa screening has been shown to vary by SES in other developed countries (Carrasco-Garrido et al, 2014;Dimitrakaki et al, 2009;Ross et al, 2007;So et al, 2014;Tabuchi et al, 2015;Weber et al, 2013). In general cancer screening is most frequent among individuals belonging to high SES because of better knowledge and higher access to medical care.…”
Section: Introductionmentioning
confidence: 99%
“…We employed conditional logistic regression analyses 19,20 to model within-individual changes in preventive care and health behaviors associated with within-individual changes in health insurance status. One set of models was unadjusted, while a second set was adjusted for factors that may both change year to year and influence preventive care and health behaviors: income level, 21,22 employment status, 23 total health care expenditures, 24 the number of office visits to health care providers, 25,26 the number of medication prescriptions, 24 availability of a usual source of care, [27][28][29][30] and health status. 31 An advantage of conditional logistic regression in this context is that it simultaneously models individual increases or decreases in preventive care and health behaviors associated with individual gain or loss of insurance, providing a more robust estimate of the effects of insurance change (approximately doubling the sample size of those changing insurance status) and yielding an average of the effects of insurance gain and loss.…”
mentioning
confidence: 99%
“…In spite of methodological limitations (Levy and Meltzer 2008), studies reviewing the impact of lack of health insurance have demonstrated that the uninsured have limited access to care; receive fewer preventive, ambulatory, and hospital-based services; and experience worse health outcomes compared with individuals who have insurance (Freeman et al 2008;Hoffman and Paradise 2008;Institute of Medicine 2002, 2009Ross and Mirowsky 2000). The uninsured are also more likely to delay seeking medical care and to receive care from emergency departments or outpatient clinics, are less likely to have a usual source of care, experience longer waits for treatment and less appropriate care for chronic conditions, and have more progressed disease states at diagnosis (Guendelman, Angulo, and Oman 2005;Ross et al 2007;Seccombe and Amey 1995 (Institute of Medicine 2002:165). Not only does lack of insurance affect health outcomes, but the uninsured experience downward social mobility in the form of job loss and personal bankruptcy when health bills come due (Boushey 2005;Dranove and Milenson 2006;Himmelstein et al 2009).…”
Section: Spillover Effects Of the Uninsuredmentioning
confidence: 99%